Vipera snakebite in Europe: a systematic review of a neglected disease. (20th July 2020) - Paolino, G.; Di Nicola, M.R.; Pontara, A.; Didona, D.; Moliterni, E.; Mercuri, S.R.; Grano, M.; Borgianni, N.; Kumar, R.; Pampena, R.
Abstract: In 2009, snakebites were included in the list of the World Health Organization (WHO) neglected diseases. Dermatological literature lacks current and up‐to‐date articles about snakebites and their management, despite the fact that dermatologists, especially from rural hospitals, can be called into the emergency room to consult the management of suspected snakebites. In this systematic review, we highlighted the main clinical and laboratory aspects of snakebites from Vipera spp. in Europe, by reviewing 3574 studies initially retrieved from PubMed, Embase and Cochrane CENTRAL databases. Of these, 78 were finally included in the systematic review. We found that the most involved taxon was V. berus in 63.3% and the most involved anatomic site of the bite was the upper limbs 53.1% with fang marks reported in 90.5%. The mean age of the patients was 32.9 years, and bites were slightly more common among males (58.2%). A wound washing was performed in 86.9% of cases before the hospitalization. The most frequently reported grade of envenomation was G2 (42.2%). In addition to local dermatological symptoms (extended erythema, oedema, cutaneous necrosis, hives, purpura, petechiae, acute compartment syndrome), numerous systemic symptoms have also been reported, including fatigue (14.4%), pain (75.3%), fever (49.2%), direct anaphylactoid reaction (5.3%), anxiety (60.8%), cranial nerve neurotoxicity (14.8%), dysesthesia/paraesthesia (7.9%), vomiting (33.7%), abdominal pain (23.3%), diarrhoea (15.4%), dyspnoea (6.3%), proteinuria (10.6%) and haematuria (9.3%). Secondary infections were present in 3.5% and disseminated intravascular coagulation in 3.1% of cases, and fasciotomy was performed in 4.2% cases, while an amputation in 6.9%. Only 0.9% of patients died. Antivenom was administered in 3053 cases. In conclusion, there is a pressing need for robust multi‐centre randomized control trials, standardized protocol for snakebite management and antivenom administration across Europe and a National snakebite register for each European country.